The effects of atrasentan on urinary metabolites in patients with type 2 diabetes and nephropathy. Issue 5 (22nd February 2017) - Pena, Michelle J.; de Zeeuw, Dick; Andress, Dennis; Brennan, John J.; Correa‐Rotter, Ricardo; Coll, Blai; Kohan, Donald E.; Makino, Hirofumi; Perkovic, Vlado; Remuzzi, Giuseppe; Tobe, Sheldon W.; Toto, Robert; et al.
Abstract : We assessed the effect of atrasentan therapy on a pre‐specified panel of 13 urinary metabolites known to reflect mitochondrial function in patients with diabetic kidney disease. This post‐hoc analysis was performed using urine samples collected during the RADAR study which was a randomized, double‐blind, placebo‐controlled trial that tested the effects of atrasentan on albuminuria reduction in patients with type 2 diabetes and nephropathy. At baseline, 4 of the 13 metabolites, quantified by gas‐chromatography mass spectrometry, were below detectable levels, and 6 were reduced in patients with eGFR < 60 mL/min/1.73 m 2 . After 12 weeks of atrasentan treatment in patients with eGFR < 60 mL/min/1.73 m 2, a single‐value index of the metabolites changed by −0.31 (95%CI −0.60 to −0.02; P = .035), −0.08 (−12 to 0.29; P = .43) and 0.01 (−0.21 to 0.19; P = .913) in placebo, atrasentan 0.75 and 1.25 mg/d, respectively. The metabolite index difference compared to placebo was 0.13 (−0.17 to 0.43; P = .40) and 0.35 (0.05‐0.65; P = .02) for atrasentan 0.75 and 1.25 mg/d, respectively. These data corroborate previous findings of mitochondrial dysfunction in patients with type 2 diabetes, nephropathy and eGFR < 60 mL/min/1.73 m 2, suggesting that atrasentan may prevent the progression of mitochondrial dysfunction common to this specific patient population. Future studies of longer treatment duration with atrasentan are indicated.